ナンキョク エイセイ ケイカク - 福西, 浩; フクニシ, ヒロシ; FUKUNISHI, Hiroshi (国立極地研究所, 1979)
P(論文) 南極地城の観測は,近年急速に進歩しつつある人工衛星の応用技術を取り入れることにより,飛躍的に発展する可能性がある.当面応用できるものとして,1)南極地域から自国への通信手段,2)南極地域内での通信手段,3)南極地城のリモートセソシソグ,4)電離圏・磁気圏の直接観測,が考えられる.この論文では,それらの内容を検討し,実現可能な衛星計画を提案する. Observations and communications in the Antarctic region will be greatly developed by using satellites. The satellite technology is applied to : 1) communications between the stations in the Antarctic region and their mother countries, 2) domestic communications in the Antarctic region, 3) remote sensings of the Antarctic region, 4) observations of the ionosphere and the magnetosphere in the polar reeion.In this paper, possibilities of these applications are discussed, and an Antarctic satellite project is proposed. departmental bulletin paper